ANALISIS EFISIENSI PRODUKSI USAHA BATIK SKALA KECIL DENGAN PENDEKATAN STOKASTIK FRONTIER DI PEKALONGAN - JAWA TENGAH - Sudantoko, Djoko; Arif, Himawan (PRESTASI, 2010)
This research was conducted in small-sized firms that operate in producing batik in Pekalongan. The purposes of this study are to contribute to the understanding of factors affecting the production of batik in the small sized firms, to estimates the efficiency level of production. There are 150 small scaled batik producers were involved in this study. The sample was taken using multistage sampling method. Statistic descriptive analysis is used to give description on the profile of small sized firms. Stochastic frontier production function was used to estimate the level of efficiency in production. The results show that variables raw material, labor, factory overhead, kerosene, and firewood positively and significantly affect the production of batik in small sized industries. However, equipment and scope of business have no significant effect on the production. Results also show technically efficiency level which varies from 0.607 to 0.959 and its average is 0.867 that indicates inefficiency and needing some improvements in production. Keywords: empowerment, small industry, batik, production, eficiency, Pekalongan, Indonesia